Sosialisasi tentang Pentingnya Tingkat Pengetahuan Gzi Ibu dan Tingkat Konsumsi Makanan dalam Mencegah Terjadinya KEK pada Ibu Hamil - Sari, Weni Kurnia; Deltu, Sri Nova (Journal Of Human And Education (JAHE), 2024)
Factors causing Chronic Energy Deficiency (CHD) in pregnant women are caused by direct and indirect factors. The direct contributing factors of Chronic Energy Deficiency (CHD) in pregnant women are inadequate nutrient consumption and illness. Indirect causative factors are inadequate food supply, inadequate parenting and inadequate environmental health and health services. The aim is to increase the awareness of pregnant women about the importance of the level of nutrition knowledge and the level of food consumption in preventing the occurrence of SEZ in pregnant women. This community service activity is carried out in the form of counseling aimed at increasing understanding and awareness of pregnant women about the importance of the level of maternal nutritional knowledge and the level of food consumption in preventing the incidence of SEZ in pregnant women in the Lubuk Buaya area. pregnant women who experience Chronic Energy Deficiency (SEZ) there are about 25 (71.4%) respondents, the rest are not Chronic Energy Deficiency (SEZ) 10 (28.6%). nutritional knowledge of mothers is mostly lacking 19 (54.3%), sufficient knowledge 7 (20%), and good knowledge 9 (20%). (20%), and good knowledge 9 (25.7%). The normal level of food consumption was 4 (11.4%), the sufficient level was 5 (14.3%), and the deficient level was 26 (74.3%). Keywords: SEZ, nutrition knowledge of pregnant women, food consumption